Plastics materials - Brydson, J. A. (Butterworth-Heinemann, 1999)
Provides an overview of the nature, manufacture, structure, properties, processing, and applications of commercially available plastics materials. This revised and updated edition adds new chapters on materials selection and special polymers, including biodegradable and electroconductive polymers and thermoplastic elastomers. In addition, many new plastics materials are added throughout and more information is included on testing methods and data.